Vocalizations of the mice Reithrodontomys soderstromi and Thomasomys paramorum (Rodentia: Cricetidae) in the province of Carchi, Ecuador - Jorge Brito M.; Diego Batallas R. (ACI Avances en Ciencias e Ingenierías, 2014)
We report descriptive information on the vocalizations of two species of rodents, analyzing and describing their spectral and temporal variability. Reithrodontomys soderstromi emits a nearly constant sounding whistle with a mean dominant frequency of 10.16 ± 0.20 kHz. The vocalizations of Thomasomys paramorum resemble clicks with frequency modulations with a mean dominant frequency of 1.74 ± 0.10 kHz and generates a harmonic whose mean frequency is 3.64 ± 0.24 kHz.